Smart Music Playlist Management System: Personalized and Collaborative Music Experience (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The goal of the Music Playlist Management System project is to provide an intuitive program that allows users to easily organise their music playlists. Among the primary goals is the provision of user-specific music suggestions based on their tastes, as well as the ability for users to build, modify, and share playlists. An extensive music library will be accessible through the app's secure user registration and authentication, powerful playlist management capabilities, and user-friendly song search function, all of which are connected to music APIs. The system's goal is to improve the music experience for users who are passionate about music and are open to collaborating with others. The project's backend will be built with Node.js or Python, while the frontend will use HTML, CSS, and JavaScript (React or Vue.js). The database will be MongoDB or PostgreSQL. The budget will centre on development expenses, API licensing fees, and continuing maintenance, while the timeframe consists of stages for requirements gathering, development, testing, and deployment. Making sure APIs are reliable and handling user privacy issues are two possible obstacles. We want to further enhance the music listening experience through excellent playlist management with future enhancements that include offline access and advanced social capabilities.